Facilities of information technology in construction industry - Abdul Kareem, Hassan Issa; Bakar, Abu Hassan Abu (2008)
The work of many authors involved in construction described and documented the interesting development and increasing in use of Information Technology (IT). These works reveals that data and information of construction industry had been entered in and/or generated by software programs and represented in many different formats used by the many disciplines involved in the industry. The increasing in use of IT is because of its facilities in all the ramifications of construction industry. The purpose of this study is to focus on the facilities that IT provides by presenting suitable application in one of the construction industry organizations. Methodology of this study is highlighting the benefits, roles, drivers, advantages and disadvantages of using IT in construction industry to clarify facilities that can be gated by implementing IT in construction industry and the reality of the event IT in implementation process. A comprehensive and extensive review of literatures ranging from books, theses and articles were carried out to establish the framework of the study that covers IT and its application in construction industry. Preliminary finding of this study proves the important effect of applying IT in construction industry by its facilities through the many activities of construction process. Also using IT can reduce some documentation problems, improves coordination and collaboration among firms participating in construction projects and leading to better communication practices.